Beginning Reading Ability with the Utilization of Flash Card Media for Students - Suciati, Irma; Alik Mustafidal Laili, (Jurnal Pendidikan Tambusai, 2023)
The purpose of this study is to describe the ability of beginning reading with the utilization of flash card media in grade I students of SDN 2 Bendilwungu. Beginning reading skills in the lower grades play an important role in determining the basis for success in student learning activities and also become an asset for students to improve their ability to seek information or knowledge. Unfortunately, students now spend more time in front of gadget screens or watching TV, this is a challenge for teachers to create innovations in learning to attract students to improve their ability to read early using flash card media. This research uses qualitative research. The subjects of this study were first grade students totaling 17 students. The research techniques used were oral tests, interviews, and documentation. Data analysis techniques use data collection techniques, data reduction, data presentation, and conclusion drawing. The results of the research on the ability of first grade students' beginning reading with the utilization of flash card media showed that 10 out of 17 students were in the very good category, 3 students were in the good category, 2 students in the medium category, 1 student in the less category and 1 student in the very less category. So that the ability to read beginning with the utilization of flash card media for first grade students of SDN 2 Bendilwungu, Tulungagung Regency as a whole based on the average is very good.